Pendampingan Kegiatan Memberantas Buta Huruf Al Qur'an Menggunakan Metode Dirosah dan Iqra Di SMA N 2 Limboto - Hasan, Moh Rizky; Makalalag, Wilsahri Prasetya; Petta Solong, Najamuddin (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
Every Muslim is required to be able to read, write, and memorize the Al-Quran and this research aims to explore assistance in activities to eradicate Al-Quran illiteracy using the Dirosah and Iqra methods at SMA Negeri 2 Limboto. Against the backdrop of increasing awareness of the importance of Al-Qur’an literacy among students, this research examines the implementation of this method in the context of senior secondary education. This research method uses a qualitative approach by collecting data through participant observation, interviews, and document analysis. The findings show a significant increase in students' ability to read, understand, and memorize the Al-Qur’an after participating in mentoring using the Dirosah and Iqra methods. The implication of this research is the importance of introducing holistic learning methods in Al-Qur’an education in high schools to ensure deep understanding and strong skills in understanding the Islamic holy book.